Fuzzy modelling using butterfly optimization algorithm for phishing detection - Noor Syahirah, Nordin; Mohd Arfian, Ismail; Nurul Aswa, Omar (World Academy of Research in Science and Engineering, 2020)
Fuzzy system is a rule-based system by using human experts which hold the truth values or membership values to make a particular decision while fuzzy modelling is a process of identifying the fuzzy parameter. However, it is difficult to generate fuzzy parameter manually when applied on complex problem. To generate the fuzzy parameter automatically, an optimization method is required and Butterfly Optimization Algorithm (BOA) is one of the good methods to be applied. The proposed method will be utilized to produce the optimal solution in finding fuzzy parameter before implementing the fuzzy technique in the dataset chosen. Two datasets were used, namely Website Phishing Dataset (WPD) and Phishing Websites Dataset (PWD). As the result, average accuracy for WPD and PWD is 96.80% and 94.65% respectively. To be conclude, BOA shows promising results to be applied to measure the accuracy of the fuzzy modelling in phishing detection.